Wheelchair mobility performance enhancement by changing wheelchair properties: What is the effect of grip, seat height, and mass? - van der Slikke, R. M. A.; de Witte, A. M. H.; Berger, M. A. M.; Bregman, D. J. J.; Veeger, D. J. H. E. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To provide insight on the effect of wheelchair settings on wheelchair mobility performance (WMP). Methods: Twenty elite wheelchair basketball athletes of low (n=10) and high classification (n=10) were tested in a wheelchair-basketball-directed field test. Athletes performed the test in their own wheelchairs, which were modified for 5 additional conditions regarding seat height (high-low), mass (central-distributed), and grip. The previously developed inertial-sensor-based WMP monitor was used to extract wheelchair kinematics in all conditions. Results: Adding mass showed most effect on WMP, with a reduced average acceleration across all activities. Once distributed, additional mass also reduced maximal rotational speed and rotational acceleration. Elevating seat height had an effect on several performance aspects in sprinting and turning, whereas lowering seat height influenced performance minimally. Increased rim grip did not alter performance. No differences in response were evident between low- and high-classified athletes. Conclusions: The WMP monitor showed sensitivity to detect performance differences due to the small changes in wheelchair configuration. Distributed additional mass had the most effect on WMP, whereas additional grip had the least effect of conditions tested. Performance effects appear similar for both low- and high-classified athletes. Athletes, coaches, and wheelchair experts are provided with insight into the performance effect of key wheelchair settings, and they are offered a proven sensitive method to apply in sport practice, in their search for the best wheelchair-athlete combination.